THE EXTRACTION OF NATURAL DYES FROM JACKFRUIT WOOD WASTE (Artocarpus Heterophyllus Lamk) WITH WATER SOLVENT BY USING THE MICROWAVE METHOD (Jurnal Bahan Alam Terbarukan, 2018)
Currently, exploration of natural dyes is increasingly being activated and developed, especially to find natural sources of dyes from different plant species and also to develop natural dyestuff extraction process technology for textile applications. During this natural dye extraction process is done by conventional methods that require a long time and a large amount of solvent. Therefore, it is a necessary alternative to the use of "green techniques" are economical in its use. In this research, extraction of Jackfruit wood waste with the microwave by studying the extraction time required to produce the optimum yield and comparing with the conventional method (heat-reflux extraction). Both of these methods use water solvent. On the microwave-assisted extraction, the optimum extraction time at 30 minutes with the acquisition yield of 3.14% (microwave power 400 watt, the ratio of material to solvent 0.02 g/mL). whereas extraction with heat-reflux method showed the optimum extraction time of 180 minutes with a yield of 3.50%. Identification of groups of pigments contained in the Jackfruit wood waste is known categories tannins, flavonoids, and quinones. Fourier Transform Infrared Spectroscopy was used to identify the major chemical groups in the extracted dye. Description of the effects of extraction with microwave and conventional, structural damage shown in a solid surface material using by Scanning Electron Microscopy. Further, to test the application on the fabric dyeing.